Policymakers, Consider Reducing Reliability - Davidson, Brian; Hellegers, Petra; George, Biju; Malano, Hector (Frontiers in Water, 2022)
In this study, the physical and economic impacts of four policy measures (crop diversification, improved watershed development, canal lining and reducing the level of reliability) all designed to improve bulk water supply, are assessed in a case study of the Musi catchment of India. The aim is to compare the impacts these policy measures have on the amount of bulk water supplied and the net economic returns across a complex multi-nodal catchment. It is argued that because it is policymakers who make decisions regarding these measures, an assessment of the private benefits to a subset of users would not be adequate. Rather, the society wide costs and benefits need to be considered. Using a hydroeconomic model of the catchment it was found that reducing the level of reliability was the most beneficial outcome from both a physical and economic perspective. The other three measures were found to have some adverse impacts on regions not directly affected by the measure.